Early pathological changes of peri-coronal tissue in the distal area of erupted or partially impacted lower third molars - Dardo Menditti; Pierluigi Mariani; Diana Russo; Barbara Rinaldi; Luca Fiorillo; Marco Cicciù; Luigi Laino (BMC, 2023)
Abstract Aim This study was performed to histologically evaluate peri-coronal tissues of partially impacted and erupted third molars that did not exhibit pathologic peri-coronal radiolucency. Materials and methods Healthy patients with erupted or partially erupted (with part or all of the dental crown present in the oral cavity) mandibular third molars (classified as IA and IIA according to the Pell and Gregory classification) and vertically positioned (according to the Winter classification or erupted third molars) associated with peri coronal radiolucency of equal to or less than 2.5 mm. Associated with third molar surgery, tissue sampling from the distal area was performed, which was subjected to an anatomopathological examination to determine the histological nature. Results One hundred teeth (100 patients) were selected, and 100 specimens were analyzed. 53% of the sample were included in the non-pathological group and 47% showed pathological changes (fibrotic tissue (n 15), periodontal cyst-like (n 9), squamous epithelial metaplasia (4 cases), islands of odontogenic epithelial residues organized micro-cyst with keratocystic/ameloblastic appearance (4 cases), granulation tissue (n 8), giant cell tumour (n 4) and lobular capillary hemangioma (n 4)). Pathological changes did not have differences in incidence between the gender (p value = 0.85) and did not show any correlation with age, (p value = 0,96). Conclusions These findings suggest that radiographic appearance may not be a reliable indicator of the absence of disease within a dental follicle. Therefore, clinicians should pay attention to or follow up on even peri-coronal radiolucency of less than 2.5 mm.